Constitutive Formulations for Non-Colloidal Suspensions - Siginer, D (Elsevier B.V., 2022)
This work is a comprehensive overall view of a complex field still far from being settled on firm grounds, that of the constitutive structure of non-colloidal suspensions. Suspensions in industrial manufacturing processes are prevalent across a spectrum of diverse industries. It is critically important that the behavior of non-colloidal suspensions under forcing is predicted on a sound basis from an industrial operational point of view not to mention the fundamental scientific significance, thus the raison d’être of the present work, a comprehensive up-to-date review of constitutive equations formulated to describe the flow of suspensions either dilute or dense under driving forces. This review only takes up the formulation of constitutive structures for non-colloidal suspensions and does not get into the rheology of suspensions per se. Thus, it is substantially more comprehensive in that sense than other reviews, which may have been published over the last two decades. It is also written not only for researchers in the field, but for those in related fields as well who may find it interesting, useful and related to their own research. Efforts have not been spared to be thorough in the presentation with commentaries about the successes and failures of each theory in their historical context and the reasons behind them. The link between different theories and the naturally unfolding succession of theories over time borne out of the necessity for better predictions as well as the challenges in the field at this time are given much emphasis at the expanse of a detailed in-depth account of various theories. For a detailed in-depth exposition, the reader is referred to the extensive reference list. © 2022 Elsevier B.V.